(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article covers the history of cooperation between the Republic of Uzbekistan and the Russian Federation in the field of medicine during the years of independence. It analyzes the ongoing research in the field of medicine, the exchange of experience, cooperation between the two countries in the training of scientific personnel. The history of cooperation in this area has also been scientifically studied. In particular, in the development of medicine, the Russian Empire began to provide medical assistance to the population of the region after the conquest of Central Asia.